Implementasi Penilaian Pembelajaran Anak Usia Dini di Kota Palangka Raya - Herlianti Herlianti; Saudah Saudah; Aghnaita Aghnaita; Muhammad Syabrina (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
The implementation of the learning assessment at Rahmat Al-Falah Palangka Raya Kindergarten which has been carried out properly every day by referring to 6 aspects of early childhood development, namely religious and moral, cognitive, physical-motor, language, social emotions and children 's arts values as stated in the Child Development Achievement Level Standard (STPPA). This study aims to describe the implementation of early childhood learning assessments in Rahmat AlFalah Palangka Raya Kindergarten. This research uses qualitative research methods with a descriptive approach. The primary data sources are 2 (two) Group B3 teachers and 24 students, as well as the Head of Kindergarten Rahmat Al-Falah as an informant Data mining uses observation techniques, interviews and documentation that are validated using triangulation techniques and sources. Furthermore, an analysis was carried out with 4 stages, namely data collection, data reduction, data presentation and drawing conclusions. The results showed that the implementation of learning assessments was carried out by teachers every day using the Daily Assessment Format which refers to the Child Development Achievement Level Standard (STPPA) with 8 principles. The growth assessed is weight, height and head circumference in each child. Meanwhile, thedevelopment assessed includes 6 aspects of development, namely religious and moral values, cognitive, physical-motor, language, social emotions and art. The types of learning assessments used such as observation, question and answer, anecdotal notesand work results, types of learning assessment reporting in the form of learning outcomes report books or report cards in writing in the form of descriptions or narratives and checklists on child development.